Prevalence and risk factors for hearing loss in high‐risk neonates in Germany. (2nd June 2019) - Thangavelu, Kruthika; Martakis, Kyriakos; Fabian, Silke; Venkateswaran, Mahima; Roth, Bernhard; Beutner, Dirk; Lang‐Roth, Ruth
Abstract: Aim: Hearing loss in infants is often diagnosed late, despite universal screening programmes. Risk factors of hearing impairment in high‐risk neonates, identified from population‐based studies, can inform policy around targeted screening. Our aim was to determine the prevalence and the risk factors of hearing loss in a high‐risk neonatal population. Methods: This was a retrospective cohort study of neonates hospitalised at the University Hospital Cologne, Germany from January 2009 to December 2014 and were part of the newborn hearing screening programme. Multivariable regression analyses using the lasso approach was performed. Results: Data were available for 4512 (43% female) neonates with a mean gestational age at birth of 35.5 weeks. The prevalence of hearing loss was 1.6%, and 42 (0.9%) neonates had permanent hearing loss. Craniofacial anomalies, hyperbilirubinaemia requiring exchange transfusion, oxygen supplementation after 36 weeks of gestation and hydrops fetalis showed associations with permanent hearing loss. Conclusion: Our findings of risk factors for hearing loss were consistent with other studies. However, some commonly demonstrated risk factors such as perinatal infections, meningitis, sepsis and ototoxic drugs did not show significant associations in our cohort. Targeted screening based on risk factors may help early identification of hearing loss in neonates.